2015
DOI: 10.1007/s00417-015-3208-7
|View full text |Cite
|
Sign up to set email alerts
|

Extensively and pan-drug resistant Pseudomonas aeruginosa keratitis: clinical features, risk factors, and outcome

Abstract: XDR and PDR Pseudomonas aeruginosa keratitis are extremely difficult to treat. Globe salvage was possible in all cases; however, more than half required therapeutic grafts. Close monitoring of patients with known ocular and systemic factors is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 27 publications
0
59
0
2
Order By: Relevance
“…In addition P. aeruginosa acquires spontaneous genetic mutations based on the antibiotic therapy and the environment and transfers those mutated genetic elements horizontally between cells, further reducing its susceptibility to antibiotics [63]. Recently, it was reported that inappropriate use of antibiotics along with other risk factors caused a breakthrough resistance in P. aeruginosa , which resulted in emergence of multi-drug resistant (MDR), extensively drug resistant (EXD) and pan-drug resistant (PDR) P. aeruginosa strains with no or minimum effective antibiotic therapy [63, 64]. Encounter with these highly resistant bacteria poses immense therapeutic challenge.…”
Section: Antibioticsmentioning
confidence: 99%
“…In addition P. aeruginosa acquires spontaneous genetic mutations based on the antibiotic therapy and the environment and transfers those mutated genetic elements horizontally between cells, further reducing its susceptibility to antibiotics [63]. Recently, it was reported that inappropriate use of antibiotics along with other risk factors caused a breakthrough resistance in P. aeruginosa , which resulted in emergence of multi-drug resistant (MDR), extensively drug resistant (EXD) and pan-drug resistant (PDR) P. aeruginosa strains with no or minimum effective antibiotic therapy [63, 64]. Encounter with these highly resistant bacteria poses immense therapeutic challenge.…”
Section: Antibioticsmentioning
confidence: 99%
“…The carbapenems antibiotics are commonly used in human multi-resistant pseudomonas infections. The lack of apparent resistance of P. aeruginosa strains to imipenem should be highlighted, especially when compared to those findings obtained from cases of human P. aeruginosa isolates, in which the in vitro resistance can reach 4% (Mohammadpour et al, 2011) to 40% (Fernandes et al, 2015). Although this drug is rarely used in veterinary medicine and is not approved for use in animals by the Food and Drug Administration, veterinarians can legally prescribe imipenem as an extra-label drug for ocular infections consisting of multi-resistant strains of P. aeruginosa.…”
Section: Susceptibility Testsmentioning
confidence: 90%
“…Risk factors for multiple and extremely drug resistance Pseudomonas include: bandage contact lens, topical steroids, previous corneal graft and ocular surface disease following Steven Johnson disease [28].…”
Section: Epidemiology P Aeruginosa Keratitismentioning
confidence: 99%